2022
DOI: 10.1016/j.redox.2021.102225
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria in human neutrophils mediate killing of Staphylococcus aureus

Abstract: Background Neutrophils play a role in innate immunity and are critical for clearance of Staphylococcus aureus . Current understanding of neutrophil bactericidal effects is that NADPH oxidase produces reactive oxygen species (ROS), mediating bacterial killing. Neutrophils also contain numerous mitochondria; since these organelles lack oxidative metabolism, their function is unclear. We hypothesize that mitochondria in human neutrophils contribute to the bactericidal capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(49 citation statements)
references
References 40 publications
1
46
0
Order By: Relevance
“…In conclusion, these data indicate that the vital release of genetic material from neutrophils is always dependent on ROS originating from either NADPH (42) or mitochondria (44,50). These extracellular DNA fibers have been proposed to boost autoimmune responses in SLE (43) or to exert anti-microbial functions (48).…”
Section: Vital Release Of Extracellular Dna From Neutrophilsmentioning
confidence: 83%
See 1 more Smart Citation
“…In conclusion, these data indicate that the vital release of genetic material from neutrophils is always dependent on ROS originating from either NADPH (42) or mitochondria (44,50). These extracellular DNA fibers have been proposed to boost autoimmune responses in SLE (43) or to exert anti-microbial functions (48).…”
Section: Vital Release Of Extracellular Dna From Neutrophilsmentioning
confidence: 83%
“…According to this model, neutrophils survive as anucleated cytoplasts while still retaining their ability to crawl or exert phagocyte functions (48). Mitochondrial DNA is a negligible component of these early NETs induced by S. Aureus (47), but mitochondrial complex III and mtROS contribute to their formation (50).…”
Section: Vital Release Of Extracellular Dna From Neutrophilsmentioning
confidence: 99%
“…A recent study found that inhibition of complex III (cytochrome c reductase) with antimycin A can significantly reduce neutrophil superoxide O 2 – production ( 17 ). MitoTEMPO can accumulate in mitochondria and reduce superoxide.…”
Section: Respiratory Burstmentioning
confidence: 99%
“…Pre-incubation of neutrophils with MitoTEMPO can significantly attenuate neutrophils’ ability to kill Staphylococcus aureus. This effect is not enhanced by co-incubation with MitoTEMPO and antimycin A, suggesting that electron transport complex III is critical for mROS production and required for the bactericidal function of neutrophils ( 17 ). Rice et al.…”
Section: Respiratory Burstmentioning
confidence: 99%
“…Neutrophils are the most profuse leukocytes, representing 50%–70% of all the circulating leukocytes in human, and are regarded as body’s first responders to injury, infections, and inflammation ( 1 , 2 ). In response to infection-associated signals, neutrophils initiate multiple effector functions such as the production of neutrophil extracellular traps (NETs), generation of reactive oxygen species (ROS), and production of antibacterial peptides to eradicate pathogens ( 3 , 4 ). The functional importance of neutrophils had been overlooked previously on the basis of their reported short life span; however, recent studies suggesting that they can survive in the circulation from 19 h to 5 days have ensured renewed attention toward the role of neutrophils under varying biological conditions ( 5 ).…”
Section: Introductionmentioning
confidence: 99%